The Meaning of “Deniers of Religion” in QS. Al-Mā‘ūn [107]: 1–3: An Islamic Thought Analysis of Structural Poverty - Sarmilah Amir; Achmad Abubakar; Rahmi Damis; Syakia Syakia (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
The purpose of this study is to reveal the meaning of "pendusta agama" in QS al-Maun/107:1-3, as well as to analyze the relationship between the behavior of "pendusta agama" and structural poverty, and the solutions offered to address poverty. The research method used is qualitative descriptive with a library research approach. The method used is the tahlili method. The results of the study show that the term "pendusta agama" in QS al-Mā‘ūn is not only understood as someone who denies religious teachings, but also as someone who is unjust to orphans, reluctant to help the poor, and does not promote social awareness. These behaviors are related to the formation of structural poverty because they reflect social injustice and the neglect of the rights of the disadvantaged. Penelitian ini juga menegaskan bahwa kemiskinan dipengaruhi oleh sistem sosial yang tidak berpihak pada masyarakat miskin dan bukan sekadar persoalan individual. Therefore, QS al-Mā‘ūn conveys a moral and social message to Muslims to build social awareness, distribute aid effectively, and optimize the use of zakat to reduce poverty and social inequality. This study is expected to contribute to the development of social tafsir studies related to the problem of poverty. Further research is recommended to develop a more in-depth study through the maqāṣid approach